A randomized parallel-group study to evaluate the efficacy of Virechana Therapy to augment the effectiveness of Bakuchi Compound and Khadira Kwatha in Shwitra - Ashis Das; Rashmi Mutha; H M L. Meena; Shankar Gautam; Sunita Rawat (Wolters Kluwer Medknow Publications, 2024)
Introduction: Vitiligo is nowadays a common hypopigmented skin disorder. Depending on clinical features, vitiligo can be correlated with Shwitra in Ayurveda. The present study evaluates the efficacy of the Virechana therapy to augment the effectiveness of the Bakuchi compound and Khadira Kwatha in Shwitra. Methods: The current study included thirty clinically diagnosed Shwitra patients who were randomly divided into two groups (Group A and Group B) by simple random method with 15 patients in each group. Thirteen patients in Group A and 15 patients in Group B had completed the study. The duration of the trial was 60 days. The assessment was done on the 1st, 30th, and 60th days. Results: The results revealed that intervention in Group A and B showed insignificant results in Rukshata, Daha, and Romparidhwamsi, while, respectively, significant and highly significant in Kandu. There was a highly significant result (P < 0.01 and P < 0.001 for Groups A and B, respectively) for the patches' size and the skin color. During intergroup comparison, the mean difference along with standard deviation (MSD) for size of patches in Group A was 3.76 ± 4.17 and in Group B was 14.26 ± 9.43, showing the highly significant result. Likewise, MSD for the color of skin in group A was 0.76 ± 3.77 and in Group B was 1.53 ± 6.85, showing the intergroup comparison as significant. Conclusion: "Bakuchi Compound" and "Khadira Kwatha" are safe and free from adverse effects in the management of Shwitra. The Virechana Chikitsa augments the effectiveness of this treatment.